2014
DOI: 10.1007/s12034-014-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloy content on microstructure and microchemistry of phases during short term thermal exposure of 9Cr-W-Ta-0⋅1C reduced activation ferritic/martensitic (RAFM) steels

Abstract: This paper presents the results of an experimental study on the microstructural evolution in 9Cr reduced activation ferritic/martensitic steels during short term thermal exposures. Since the microstructure is strongly influenced by the alloying additions, mainly W, Ta and C contents, the effect of varying W and Ta contents on the martensite structure that forms during normalizing treatment and the subsequent changes during tempering of the martensite in the temperature regime of 923-1033 K have been studied. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Although yttrium addition improves the property of the RAFM steel [9,10], all of the previous studies have added Y 2 O 3 with an yttrium mass fraction exceeding 0.15wt-% to the ODS-RAFM steel. When present in excessive amounts, the yttrium segregates and many yttrium-rich blocks appear in the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Although yttrium addition improves the property of the RAFM steel [9,10], all of the previous studies have added Y 2 O 3 with an yttrium mass fraction exceeding 0.15wt-% to the ODS-RAFM steel. When present in excessive amounts, the yttrium segregates and many yttrium-rich blocks appear in the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…(i) presence of the small exothermic peak at a temperature higher than M s in the DSC thermogram of 1?4W steel corresponding to M 3 C precipitation, which is supported by TEM results, as reported in the section on 'Thermal analysis study of 1?4W steel' (ii) temperature interval between M s and M f is ,100 and 50 K for 1W and higher W steel respectively (Table 2); an autotempering process, if it happens, should be more pronounced in 1W rather than in 1?4 or 2W steels, whereas experimental results prove the contrary (iii) the presence of the carbides has been observed in relatively wide laths of low dislocation density; formation of such wide laths implies the self-diffusion of Fe and substitutional solutes, which is favoured at higher temperatures 51 and is sluggish below the M s temperature; in our earlier study, 55 no significant coarsening of laths was observed during tempering of martensite even until 2 h at 1023 K, a temperature far higher than M s ; hence, the observed coarse laths correspond to ferrite formed at temperature higher than M s (iv) analysis of the SAED pattern of 1?4W steel normalised at 1253 K given in Fig. 4b showed the presence of M 3 C and a-Fe along [0 2 21] and [0 21 2] zone axis respectively; a stereographic analysis of the above diffraction pattern did not satisfy the following Bagaryatsky orientation relationship 56,57 between ferrite and cementite, which results from the decomposition of martensite during initial stages of tempering…”
Section: Discussionmentioning
confidence: 60%
“…the presence of the carbides has been observed in relatively wide laths of low dislocation density; formation of such wide laths implies the self-diffusion of Fe and substitutional solutes, which is favoured at higher temperatures 51 and is sluggish below the M s temperature; in our earlier study, 55 no significant coarsening of laths was observed during tempering of martensite even until 2 h at 1023 K, a temperature far higher than M s ; hence, the observed coarse laths correspond to ferrite formed at temperature higher than M s…”
Section: Discussionmentioning
confidence: 66%
“…A taxa de coalescimento na matriz ferrítica aumenta com a adição de Mn e diminui com a adição de V e W, uma vez que estes elementos de liga alteram o coeficiente de difusão do Cr na matriz. No entanto, V é mais eficaz que W. Em maiores intervalos de envelhecimento, o teor de V no carboneto aumenta e substitui os átomos de Fe e W, desta maneira desempenha um papel fundamental no controle do coalescimento desta fase [10][11][12][13]. A composição química LFN1 teoricamente apresentará menores taxas de coalescimento, já que possui o menor teor de Mn e o maior teor de V entre as composições simuladas.…”
Section: Diagramas De Fração De Fase Em Função Da Temperatura -Estágiunclassified